2021
DOI: 10.3390/designs5030056
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Dynamic Hands-Free Door Opener to Prevent COVID-19 Pandemic Spreading

Abstract: The situation caused by COVID-19 has shown several vulnerabilities in the attitudes and habits of modern society, inducing the need to adopt new behaviors that will directly impact daily activities. The quickly spreading virus contaminates the surfaces of handles and objects, and subsequent contact with the eyes, nose, or mouth is one of the main contagion factors. There is an urgent need to rethink how we interact with the most-touched surfaces, such as door handles in public places with a high flux of people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…To this aim a leaf-based concept had already been presented and tested by Maranha et al in [ 22 ] revealing that the participants found no problem with the usability of the auxiliary item depicted in Fig. 10 .…”
Section: Testingmentioning
confidence: 99%
“…To this aim a leaf-based concept had already been presented and tested by Maranha et al in [ 22 ] revealing that the participants found no problem with the usability of the auxiliary item depicted in Fig. 10 .…”
Section: Testingmentioning
confidence: 99%
“…The recent pandemic of COVID-19 has shown how 3D printing technologies have been able to rapidly adapt and to respond to the need of crucial healthcare supplies, such as, for example, components for respirators, medical glasses, face shields, hands-free door openers, mask adjusters, ventilator splitters, oxygen filter housings, etc. [29] , [30] , [31] , [32] , [33] , [34] . Among these supplies, those for which a very large number of designs was proposed were face shields, respirators, and hands-free devices to limit the diffusion of the virus [29] , [31] , [32] , [33] , [34] .…”
Section: Introductionmentioning
confidence: 99%
“… [29] , [30] , [31] , [32] , [33] , [34] . Among these supplies, those for which a very large number of designs was proposed were face shields, respirators, and hands-free devices to limit the diffusion of the virus [29] , [31] , [32] , [33] , [34] . Nevertheless, the works dealing with the design of hands-free door openers [32] , [33] , [34] focus very often on aesthetic and manufacturing aspects, without considering an automatic numerical design procedure involving modern generative design software, like topology optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%